The Predictive Value of PAPP-A for Threatened Miscarriage in Pregnant Women at 11–14 Weeks of Gestation: A Case-Control Study - Tam Thai Thanh Tran; Hieu Minh Pham; Hung Huynh Vinh Ly; Huyen My Bui; Tin Hoang Nguyen (Clinical and Experimental Obstetrics & Gynecology)
Background: Pregnancy-associated plasma protein A (PAPP-A) levels in the first trimester of pregnancy are important predictors of future obstetric outcomes. This study evaluated the PAPP-A levels in women with threatened miscarriage and assessed their value in the early diagnosis of this condition. Methods: We conducted a retrospective case-control study from June 2020 to December 2020, involving 122 patients: 61 pregnant women with threatened miscarriage (disease group) and 61 healthy pregnant women (control group). All participants were at gestational age of 11–14 weeks. Pregnant women were selected according to specific diagnostic criteria for threatened miscarriage, regardless of any prior bleeding. The two groups were interviewed to collect data on age, number of pregnancies, body mass index (BMI), risk factors for miscarriage, blood pressure, fetal heart rate, and other relevant parameters. Participants also underwent clinical examinations, including ultrasound scans, non-invasive prenatal testing, and rubella antibody testing. Maternal venous blood samples for PAPP-A quantification were collected at 11–14 gestational weeks. Results: The median PAPP-A concentration was significantly lower in the disease group (0.63 multiples of the median [MoM]) compared to the control group (1.09 MoM), with a p-value < 0.001. Compared to the control group, the disease group exhibited a higher proportion of underweight women (p = 0.024), along with greater gestational age (p = 0.003), crown-rump length (p = 0.005), and nuchal translucency (p = 0.002) values. The PAPP-A levels demonstrated prognostic value in pregnancy, with a cut-off point of 0.8255 MoM for the disease and control groups receiver operating characteristic (ROC) curve analysis demonstrated high sensitivity and relatively high specificity, with an area under the curve (AUC) of 0.789 (p < 0.001). Conclusions: PAPP-A demonstrates moderate predictive value for threatened miscarriage, with low PAPP-A levels being associated with this condition.